2012
DOI: 10.1039/c2cc34525k
|View full text |Cite
|
Sign up to set email alerts
|

Low-coordinate cobalt(ii) terphenyl complexes: precursors to sterically encumbered ketones

Abstract: Cobalt(II) diaryl complexes react with CO to afford Co(2)(CO)(8) and sterically encumbered ketones whose structure varies depending on the nature of the aryl ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…In the crystal structure of 1 a second twin component was detected: the twin law was (-1 0 0, 0 1 0, 0 0 -1) and the twin fraction refined to 0.336 (14). Merohedral crystal twinning [twin law (0 1 0, 1 0 0, 0 0 -1)] was detected for 2 and the twin fraction refined to 0.3834 (13). The hexane solvent molecule in 7•0.5C 6 H 14 was extensively disordered: because this could not be modelled sensibly using alternative atomic sites PLATON SQUEEZE 32 was used to remove the contribution of the disordered solvent to the diffraction data and allow refinement against the "solvent-free" dataset.…”
Section: Crystallographymentioning
confidence: 96%
See 1 more Smart Citation
“…In the crystal structure of 1 a second twin component was detected: the twin law was (-1 0 0, 0 1 0, 0 0 -1) and the twin fraction refined to 0.336 (14). Merohedral crystal twinning [twin law (0 1 0, 1 0 0, 0 0 -1)] was detected for 2 and the twin fraction refined to 0.3834 (13). The hexane solvent molecule in 7•0.5C 6 H 14 was extensively disordered: because this could not be modelled sensibly using alternative atomic sites PLATON SQUEEZE 32 was used to remove the contribution of the disordered solvent to the diffraction data and allow refinement against the "solvent-free" dataset.…”
Section: Crystallographymentioning
confidence: 96%
“…[13][14][15] We are interested in deducing how subtle changes in the steric pocket offered by the m-terphenyl ligands can affect the coordination environment around the metal centre, with the eventual aim to tailor the ligand sterics towards the investigation of bonding and small molecule reactivity.…”
mentioning
confidence: 99%
“…This angle is also similar to the related compound (2,6-Naph2C6H3)2CoOEt2 (Naph = 1-C10H7). 17 The torsion angle between the two central aryl rings for both 1 and 2 is slightly more acute than the corresponding interplanar angles in related two-coordinate m-terphenyl compounds. An initial assessment of the catalytic activity of 1 and 2 for the cyclooligomerisation of isocyanates was carried out using ethyl isocyanate as a model substrate in C6D6 at room temperature with 5 mol% catalyst loading (Scheme 1, Table 1, entries 1 and 4).…”
Section: Cyclotrimerisation Of Isocyanates Catalysed By Low-coordinatmentioning
confidence: 99%
“…Recent investigations within our research group have shown that cobalt(II)diaryl complexes featuring sterically demanding (2,6-Naph 2 C 6 H 3 À ) and (2,6-Mes 2 C 6 H 3 À ) (Mes= 2,4,6-Me 3 C 6 H 2 ) ligands react with carbon monoxide to afford sterically encumbered ketones, the structure of which varies depending on the nature of the aryl ligands. [26] We have chosen to utilize this sterically demanding (2,6-Naph 2 C 6 H 3 À ) ligand in the stabilization of low-coordinate Group 12 diaryl complexes. As part of our investigations into the fundamental structure and bonding of low-coordinate d-block complexes, [15,27,28] we have identified this ligand as a suitable system that offers intriguing possibilities for the coordination of metals with its Abstract: The synthesis and characterization of the first series of low-coordinate bis(terphenyl) complexes of the Group 12 metals, [Zn(2,6-Naph 2 C 6 H 3 ) 2 ] (1), [CdA C H T U N G T R E N N U N G (OEt 2 )(2,6-Naph 2 C 6 H 3 ) 2 ] (2) and [HgA C H T U N G T R E N N U N G (OEt 2 )(2,6-Naph 2 C 6 H 3 ) 2 ] (3) (Naph = 1-C 10 H 7 ) are described.…”
Section: Introductionmentioning
confidence: 99%